Comparative efficacy of different exercise methods to improve cardiopulmonary function in stroke patients: a network meta-analysis of randomized controlled trials - Wang, Chengshuo; Xu, Yanan; Zhang, Linli; Fan, Weijiao; Liu, Zejian; Yong, Mingjin; Wu, Liang (Frontiers in Neurology, 2024)
Background: Although some studies have shown that exercise has a good effect on improving the cardiopulmonary function of stroke patients, it still needs to be determined which exercise method does this more effectively. We, therefore, aimed to evaluate the effectiveness of different exercise methods in improving cardiovascular function in stroke patients through a network meta-analysis (NMA), providing a basis to select the best treatment plan for stroke patients. Methods: We systematically searched CNKI, WanFang, VIP, CBM, PubMed, Embase, Web of Science, and The Cochrane Library databases from establishment to 30 April 2023. Randomized controlled trials (RCTS) on exercise improving cardiopulmonary function in stroke patients were included, and we screened the included articles and extracted the relevant data. RevMan (version 5.4) and Stata (version 17.0) were used for data analysis. Results: We included 35 RCTs and a total of 2,008 subjects. Intervention measures included highintensity interval training (HIIT), aerobic training (AT), resistance training (RT), combined aerobicand resistance exercise (CE), and conventional therapy (CT). In the network meta-analysis, the surface under the cumulative ranking area (SUCRA) ranking result indicated that HIIT improved peak oxygen uptake (VO2peak) and 6-minute walking distance (6MWD) optimally, with rankings of HIIT (100.0%)> CE (70.5%)> AT (50.2%)> RT (27.7%)> CT (1.6%), and HIIT (90.9%)> RT (60.6%)> AT (48.9%)> RT (48.1%)> CT (1.5%), respectively. The SUCRA ranking result showed that CE improved systolic blood pressure (SBP) and diastolic blood pressure (DBP) optimally, with rankings of CE (82.1%)> HIIT (49.8%)> AT (35.3%)> CT (32.8%), and CE (86.7%)> AT (45.0%)> HIIT (39.5%)> CT (28.8%), respectively.We showed that exercise can effectively improve the cardiopulmonary function of stroke patients. HIIT was the most effective in improving VO2peak and 6MWD in stroke patients. CE was the most effective in improving SBP and DBP in stroke patients. However, due to the limitations of existing clinical studies and evidence, larger sample size, multi-center, and high-quality RCTs are needed to verify the above conclusions in the future.